13 - CODESRIA Reports: An Advanced Research Project on Peace, Security and Post-Conflict Reconstruction in the Great Lakes Region of Africa: A Reflection on a New CODESRIA’s Social Science Initiative and Its Policy Implications - Tukumbi Lumumba-Kasongo, (CODESRIA Bulletin, 2013)
Abstarct